2017
DOI: 10.3389/fpls.2017.01867
|View full text |Cite|
|
Sign up to set email alerts
|

Reciprocal Interactions between Cadmium-Induced Cell Wall Responses and Oxidative Stress in Plants

Abstract: Cadmium (Cd) pollution renders many soils across the world unsuited or unsafe for food- or feed-orientated agriculture. The main mechanism of Cd phytotoxicity is the induction of oxidative stress, amongst others through the depletion of glutathione. Oxidative stress can damage lipids, proteins, and nucleic acids, leading to growth inhibition or even cell death. The plant cell has a variety of tools to defend itself against Cd stress. First and foremost, cell walls might prevent Cd from entering and damaging th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
125
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(132 citation statements)
references
References 200 publications
5
125
1
1
Order By: Relevance
“…Therefore, the plant cell wall continously undergoes structural modifications in order to adapt to the plant's development stages and environmental conditions (Caffall & Mohnen ; Loix et al . ). Plants exposed to Cd show concentration‐dependent alterations in cell wall structure.…”
Section: Introductionsupporting
confidence: 84%
“…Therefore, the plant cell wall continously undergoes structural modifications in order to adapt to the plant's development stages and environmental conditions (Caffall & Mohnen ; Loix et al . ). Plants exposed to Cd show concentration‐dependent alterations in cell wall structure.…”
Section: Introductionsupporting
confidence: 84%
“…During Cd stress, systems capable of preventing excessive oxidation are induced or stimulated. These systems include some enzymes, such as superoxide dismutase (SOD) and peroxidases such as GPOX [24].…”
Section: Discussionmentioning
confidence: 99%
“…Different tissues of Massai grass showed different responses in the primary metabolism when plants were exposed to Cd. Nevertheless, cysteine, ornithine, arginine, tryptophan, lysine, and histidine accumulated in more than one tissue, indicating that these amino acids stress in plants is the increase in the production of reactive oxygen species (ROS), which results in oxidative damages that induce lipid peroxidation CUYPERS et al, 2010;LOIX et al, 2017), as observed in the leaves of Panicum virgatum (TAI et al, 2017). Lipid peroxidation can cause the rupture of tonoplast and change the structure and amount of chloroplasts in the cells (PARMAR; KUMARI; SHARMA, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…To scavenge ROS and decrease the damage caused by Cd to the photosynthetic apparatus, the plants increase the synthesis of enzymatic and non-enzymatic antioxidants, mainly of the ascorbate-glutathione cycle LOIX et al, 2017). Among the enzymes involved in this cycle, superoxide dismutase (SOD) acts on dismutation of superoxide (O2 -) in hydrogen peroxide (H2O2), while ascorbate peroxidase (APX), catalase (CAT) and guaiacol peroxidase (GPOX) reduce H2O2 to H2O (CUYPERS et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation